2020
DOI: 10.1039/d0sc01022g
|View full text |Cite
|
Sign up to set email alerts
|

A new azobenzene-based design strategy for detergents in membrane protein research

Abstract: Here, L. H. Urner and co-workers identify a new detergent design strategy for the non-denaturing structural analysis of membrane proteins by studying the gas-phase properties of azobenzene-based oligoglycerol detergents.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 62 publications
1
36
0
Order By: Relevance
“…It has been reported that a secondary amine can accommodate a proton better than azo groups, so that the Eand Z-isomers of the azobenzene can be Please do not adjust margins Please do not adjust margins generated and monitored by IMS. 37,39 In our study, the ATD of 2 shifted towards shorter drift time upon UV irradiation (Fig. S9).…”
supporting
confidence: 54%
See 1 more Smart Citation
“…It has been reported that a secondary amine can accommodate a proton better than azo groups, so that the Eand Z-isomers of the azobenzene can be Please do not adjust margins Please do not adjust margins generated and monitored by IMS. 37,39 In our study, the ATD of 2 shifted towards shorter drift time upon UV irradiation (Fig. S9).…”
supporting
confidence: 54%
“…IMS allows the separation of ions based on their size which makes it an especially powerful tool to analyse photoisomers with their typically identical elemental compositions and thus identical m/z values. [37][38][39] IMS has been used to analyse the topology of intertwined molecules 40 and recently both MS and IMS utilised to identify pseudorotaxanes. 25 E,E-DC and Z-L have the same m/z, Please do not adjust margins Please do not adjust margins however their isotope patterns differ as E,E-DC is doubly charged (peak spacing of 0.5) while Z-L is singly charged (peak spacing of 1.0).…”
mentioning
confidence: 99%
“…This motivated us to investigate whether regioisomer ratios would change during detergent synthesis. We applied standard protocols to synthesize the [G1] OGD regioisomer mixtures 1 – 4 , including direct alkylation ( 1 ); mesylation followed by azidation, reductive amination, and alkylation by amide coupling ( 2 ); propargylation and alkylation by copper‐catalysed click reaction ( 3 ); and mesylation followed by alkylation ( 4 ) [10a, b, 13] . Irrespective of the synthetic strategy employed, regioisomer ratios of [G1] OGDs were similar to those obtained in the starting material ( a : b , 6:4, Figure 2, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…NMR raw data can be downloaded from the OSF website (https://doi.org/10.17605/OSF.IO/TJXSR). The synthesis protocols of [G1] OGD batches 1 , 3 , and [G2] OGD batches 5 , 8 , and 9 have been reported previously [10a, b] . The protocols for the synthesis of 2 , 4 , 6 , and 7 have not been published before.…”
Section: Methodsmentioning
confidence: 99%
“…Mass-spectrometry-based techniques were already proposed as a powerful characterization tool for the structural characterization of azobenzenes, either alone 18,19 or in the presence of metals 20,21 The present work builds on these approaches to gain further information in the kinetics of the complex isomerization processes at work in bridged azobenzenes. On the one hand, we used on-line LC-UV-MS to study the kinetics of the E→Z thermal back relaxation, and particularly focused on the influence of the solvent on both the kinetics and the steady-state Z1/Z2 ratio formation.…”
Section: Introductionmentioning
confidence: 99%